Lipid Parameters are Independently Associated with Cardio-Ankle Vascular Index (CAVI) in Healthy Japanese Subjects - Daiji Nagayama; Yasuhiro Watanabe; Atsuhito Saiki; Kohji Shirai; Ichiro Tatsuno (Journal of Atherosclerosis and Thrombosis, 2018)
[Aim]: To investigate the associations of conventional lipid parameters with arterial stiffness assessed by cardio-ankle vascular index (CAVI). [Methods]: A retrospective cross-sectional study was conducted in 23,257 healthy Japanese subjects (12,729 men and 10,528 women, aged 47.1+-12.5 years, body mass index (BMI) 22.9+-3.4 kg/m2) who underwent health screening between 2004 and 2006 in Japan. [Results]: Male subjects had significantly higher BMI, CAVI and triglycerides (TG), and lower high-density lipoprotein cholesterol (HDL-C) compared to female subjects. After adjusting for confounders, including gender, age, systolic blood pressure and BMI identified by multiple regression analysis, adjusted CAVI was lower in normolipidemic than in dyslipidemic subjects. Among dyslipidemic subjects, those with hypertriglyceridemia had higher adjusted CAVI. A trend test detected linear relations between adjusted CAVI and all the conventional lipid parameters throughout the entire range of serum levels. After adjusting for confounders, logistic regression models showed that all lipid parameters contributed independently to high CAVI (>-90th percentile). Receiver-operating-characteristic analysis determined reliable cut-off values of 93 mg/dl for TG (area under the curve, AUC= 0.735), 114 mg/dl for low-density lipoprotein cholesterol (AUC=0.614) and 63 mg/dl for HDL-C (AUC=0.728) in predicting high CAVI. These cut-off values were confirmed to independently predict high CAVI in a bivariate logistic regression model. [Conclusion]: The present study demonstrated independent contribution of conventional lipid parameters to CAVI, indicating a possible association of lipid parameters with early vascular damage.